Enhancer hijacking activates oncogenic transcription factor NR4A3 in acinic cell carcinomas of the salivary glands - Haller, Florian; Körner, Cindy; Weichenhan, Dieter; Lutsik, Pavlo; Kleinheinz, Kortine; Eils, Roland; Plass, Christoph; Wiemann, Stefan (Nature Communications, 2019)
Acinic cell carcinoma (AciCC) is a rare salivary gland carcinoma that is poorly understood. Here the authors perform genomic, transcriptomic and epigenomic profiling of AciCC and find highly recurrent and specific rearrangements [t(4;9)(q13;q31)], which lead to enhancer hijacking that activates oncogenic transcription factor NR4A3.
Gesehen am 25.01.2019